D = 11 dS5 backgrounds with enhanced supersymmetry. (18th November 2022) - Farotti, D; Gutowski, J B
Abstract: We classify all warped dS 5 backgrounds in D  = 11 supergravity with enhanced supersymmetry. We show that backgrounds preserving N  = 16 supersymmetries consist of either a stack of M5 branes with transverse space R 5, or a generalized M5-brane configuration with transverse space R × N 4, where N 4 is a hyper-Kähler manifold and the M5-brane harmonic function is determined by a hyper-Kähler potential on N 4 . Moreover, we find that there are no backgrounds preserving exactly N  = 24 supersymmetries. Backgrounds preserving N  = 32 supersymmetries correspond to either R 1, 10 or A d S 7 × S 4 .